Barriers and Opportunities for Clinical Nutritionists in 13 Latin American Countries: A Qualitative Study - Tannia Valeria Carpio-Arias; Mirta Crovetto-Mattassi; Samuel Durán-Agüero; Solange Parra-Soto; Leslie Landaeta-Díaz; Sheila Cerezo de Ríos; Jhon Jairo Bejarano-Roncancio; Karla Cordón-Arrivillaga; María Vitullo; Otilia Perichart-Perera; Nathaly Vanessa Averos; Solange Anahí Rodríguez; et al. (Journal of Primary Care & Community Health, 2023)
A clinical nutritionist (CN) is a university-educated professional trained to perform preventive and recovery functions in the health of patients. The actions of these professionals, both worldwide and in Latin America, may face barriers and opportunities that require careful identification and examination. The main objective of this study is to identify the most important barriers and opportunities for the clinical nutritionist in 13 Latin American countries. A qualitative study was carried out; the initial phase involved conducting in-depth individual interviews with 89 informants, experienced CNs from 13 Latin American countries. After calculating the mean and standard deviation, we ranked the top 10 most frequently reported barriers by assigning a score ranging from 1 to 10. Additionally, 3 opportunities were identified with a lower score from 1 to 3. Means and standard deviation were calculated to sort the responses. Results: the most important barrier was the absence of public policies that regulate and/or monitor compliance with the staffing of CNs according to the number of hospital beds, while the most important opportunity was the advances in technology such as software, body analysis equipment and other tools used in Nutritional Care. The identified barriers can interfere with the professional performance of CNs and, moreover, make it difficult to monitor the good nutritional status of patients. It is recommended to consider the barriers identified in this study, as well as the opportunities, with a view to improving the quality of hospital services with an adequate supply of nutritionists.